Neurobehavioral toxicity of carbon nanotubes in mice: Focus on brain-derived neurotrophic factor messenger RNA and protein. (April 2017) - Gholamine, Babak; Karimi, Isaac; Salimi, Amir; Mazdarani, Parisa; Becker, Lora A
Objectives: The aim of this study was to evaluate neurobehavioral toxicity of single-walled (SWNTs) and multiwalled carbon nanotubes (MWNTs) in mice. Methods: Male NMRI mice were randomized into 5 groups ( n = 10 each): Normal control (NC) group was injected intraperitoneally (i.p.) with phosphate-buffered saline (PBS) solution (pH 7.8; ca. 1 mL), MW80 and MW800 groups were injected with either i.p. 80 or 800 mg kg −1 MWNTs suspended in 1 mL of PBS and SW80 and SW800 groups were injected with either i.p. 80 or 800 mg kg −1 SWNTs suspended in 1 mL of PBS. After 2 weeks, five mice from each group were evaluated for brain-derived neurotrophic factor (BDNF) messenger RNA expression and protein content of brain tissues. Locomotion, anxiety, learning and memory, and depression were measured by open field test (OFT), elevated plus-maze (EPM), object recognition test (ORT), and forced swimming test (FST), respectively. Results: Ambulation time and center arena time in the OFT did not change among groups. In the EPM paradigm, SWNTs (800 mg kg −1 ) and MWNTs (80 and 800 mg kg −1 ) showed an anxiogenic effect. In ORT, MWNTs (80 mg kg −1 ) increased the discrimination ratio while in FST, MWNTs showed a depressant effect as compared to vehicle. The BDNF gene expression in mice treated with 80 and 800 mg kg −1 SWNTs or 80 mg kg −1 MWNTs decreased as compared to NC mice although BDNF gene expression increased in mice that were treated with 800 mg kg −1 MWNTs. The whole brain BDNF protein content did not change among groups. Conclusion: Our study showed that i.p. exposure to carbon nanotubes (CNTs) may result in behavioral toxicity linked with expression of depression or anxiety that depends on the type of CNTs. In addition, exposure to CNTs changed BDNF gene expression.